Pulp mill sludges as a solution for reducing the risk of mineral nitrogen leaching from agriculture - Kinnula, Sari; Kanerva, Sanna; Soinne, Helena; Toivonen, Marjaana; Joona, Juuso; Tuulos, Antti; Parviainen, Tuure; Kinnunen, Ossi; Kivelä, Jukka (Scientific Agricultural Society of Finland, 2024)
Nitrogen (N) from agricultural systems contributes to the eutrophication of waterbodies through leaching. Incor-porating organic material with a high carbon-to-nitrogen (C/N) ratio, such as mixed pulp mill sludges (PMSs), into the soil in autumn could reduce the amount of leachable N. This study tested the potential of composted and lime-stabilised mixed PMSs (CPMS and LPMS) in reducing the concentration of mineral N in the soil, and thus the risk of N leaching from arable land in the boreal region using a two-year field experiment. To better understand the mechanismsof the PMSs for influencing mineral N concentration in soil, the impact of PMSs with different quality on the reac-tions of N in the soil was investigated in a laboratory incubation study. In the field experiment, nitrate-N (NO3--N) concentration was lower with PMSs compared to mineral fertilisation and the control during the first autumn and the following spring after PMS application. The undersowing of Italian ryegrass reduced the NO3--N concentration in the soil during the first autumn. In the incubation experiment, PMSs reduced the soil ammonium-N (NH4+-N) concentration at the beginning of the experiment and the soil NO3--N concentration throughout the experiment compared to a mineral fertiliser treatment and an organic fertiliser.Increased soil respiration in PMS-treated soils indicated increase in microbial activity, and thus immobilisation of soil NO3--N and NH4+-N due to PMSs addition. These results suggest that PMSs have the potential to reduce N leaching from agricultural soils. However, the immobilisation of N must be considered when planning the nutrient requirements of the following crops.
Keywords: soil amendment; recycled fertiliser; primary sludge; secondary sludge; nutrient recycling; nitrogen leaching